Artificial environment of habitats from space sozopsychology perspective - Terelak, Jan F. (Studia Ecologiae et Bioethicae, 2004)
The article tries to develop a theoretical and methodological basis for modeling human being's artificial environment in spaceships. The author, as a founder of "cosmic sozopsychology" understands this as a subdiscipline of sozopsychology, underlines the necessity to build a safety barrier to maintain and protect human life in an extreme cosmic environment. It demands a very detailed knowledge of man ecology including upper and bottom limits of tolerance for stressful factors existing in space. These aims are very useful for flight simulators. Among others, there are very important so-called "ecological imitators" of human work and human existence on board spaceships. The detailed knowledge of all stress factors has systematic character, including objective and subjective interactions within the human-environment system.